Towards an understanding of maltreatment in football - Newman, James A.; Rumbold, James L. (Frontiers in Sports and Active Living, 2024)
This study explored the understanding of maltreatment from the perspective of various personnel working in roles related to safeguarding and welfare in English professional and semi-professional football. Through a social constructivist position, the present study was able to explore multiple understandings and perceptions of maltreatment in football. Individual semi-structured interviews (MDuration = 68.00 minutes, SD = 9.05 minutes) were conducted with 19 participants working across league structures ranging from the English Premier League (EPL) to the English Northern Premier League Division One, as well as individuals working with some of the principal organizations in English professional football. Through reflexive thematic analysis, three general dimensions were highlighted: "current understanding of maltreatment in football," "constituents of maltreatment," and "signs and symptoms of maltreatment." Findings from those working in a safeguarding capacity mirror the research literature around understanding the components of maltreatment but also demonstrate how wrongdoing is nuanced by the football context, in that certain forms of maltreatment are driven by the unique nature of this environment. From an applied perspective, the findings also outline how to distinguish both the more overt and covert signs and symptoms of maltreatment, whilst also highlighting the impact of maltreatment on individuals' mental health and their sense of self. Overall, the findings provide a platform for practitioners and researchers to consider in the design of safeguarding and welfare provision by highlighting the need to raise knowledge and awareness of maltreatment whilst intervening to challenge the prevailing workplace culture within professional football.